Thermal analysis in optical waveguides - Ibrahim, Mohd. Haniff; Mohd. Kassim, Norazan; Mohammad, Abu Bakar; Kamsah, Nazri (Penerbit UTM Press, 2007)
A thermal analysis in optical waveguides structure is simulated in order to predict the temperature distribution over the waveguide cross-section, when heated by a heating element. A steady state heat equation is solved by using finite difference numerical method. It is observed that by applying different value of thermal conductivities for each waveguide element and further application of convection mechanism to the ambient, obvious differences with other researchers’ work are recorded